Enzyme-degradable 3D multi-material microstructures - Gräfe, David; Gernhardt, Marvin; Ren, Jiongyu; Blasco, Eva; Wegener, Martin; Woodruff, Maria Ann; Barner-Kowollik, Christopher (Advanced functional materials, 2021)
There exists a growing need for smart materials suitable for use in biomedical applications. Herein, a photoresist that can be used to fabricate a biocompatible material entirely degradable by the enzyme chymotrypsin is introduced. The photoresist is based on a crosslinker with a tyramine moiety that is recognized and cleaved by the enzyme chymotrypsin. Macroscopic films as well as microstructures are fabricated via the use of direct laser writing. Multi-material boxing ring microstructures are generated and selectively degraded by the enzyme. Cell biocompatibility studies indicate that cells are able to attach and proliferate over one week on the material. A photoresist that is biocompatible and can be entirely removed by a biocompatible stimulus such as an enzyme can potentially be used as an easily removed tissue engineering scaffold and is especially promising for basic cell biology research.